2012 IEEE Fifth International Conference on Cloud Computing 2012
DOI: 10.1109/cloud.2012.100
|View full text |Cite
|
Sign up to set email alerts
|

Survivable Virtual Infrastructure Mapping in Virtualized Data Centers

Abstract: Abstract-In a virtualized data center, survivability can be enhanced by creating redundant VMs as backup for VMs such that after VM or server failures, affected services can be quickly switched over to backup VMs. To enable flexible and efficient resource management, we propose to use a service-aware approach in which multiple correlated Virtual Machines (VMs) and their backups are grouped together to form a Survivable Virtual Infrastructure (SVI) for a service or a tenant. A fundamental problem in such a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Xu et al [10] proposed a VDC allocation scheme that considers embedding backup VMs and virtual links with the goal of minimizing consumed resources. However, they do not consider the availability of the physical machines and they also assume that the number of backups is known beforehand.…”
Section: Survivable Vdc Embeddingmentioning
confidence: 99%
“…Xu et al [10] proposed a VDC allocation scheme that considers embedding backup VMs and virtual links with the goal of minimizing consumed resources. However, they do not consider the availability of the physical machines and they also assume that the number of backups is known beforehand.…”
Section: Survivable Vdc Embeddingmentioning
confidence: 99%
“…[26] studied the SVNE problem in the context of grid-and cloud-computing survivability over optical networks, highlighting the importance of the survivable CN mapping (SCNM) problem which combines the SVNE problem and VM survivability. In this regard, the study in [13] suggested server capacity relocation and lightpath re-provisioning for virtualized datacenters to offer survivability. Ref.…”
Section: Background and Related Workmentioning
confidence: 99%
“…CN survivability for a small number of failures in the physical infrastructure has been modeled as a survivable virtual-network embedding (SVNE) problem defined as the resilient VN mapping over the physical infrastructure to avoid disconnection due to failures [9]. Most SVNE studies considered single and multiple physical-link (-node) failures (e.g., datacenter and shared-risk group (SRG)), and a regional failure that may or may not be a disaster [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The VBN technique is also often used in combination with other techniques such as VM replication, VM placement, and VM checkpoint techniques (that we have introduced before). VBN with VM replication approaches are survivable virtual infrastructure with active VM replication (SVI-Active-VM-Rep) [141] and a greedy randomized adaptive VM replication (VN-GRASP) [142]. VBN with VM checkpoint is suggested in VNsnap by [143].…”
Section: Resiliency In Cloud Integrated Infrastructurementioning
confidence: 99%